Induction of phenylalanine ammonia-lyase In groundnut cultivars in response to biotic and abiotic stress - A.D. CHOUDHARY, M.C. KALE* and (Indian Phytopathology, 2002)
Inducibility of phenylalanine ammonia-lyase (PAL) regulating the biosynthesis of antifungal phytoalexin medicarpin was studied in groundnut seedling. The expression of PAL was investigated in groundnut cultivar, Girnar1 (resistant to) and TAG-24, ICGS-IO, ICGS-76 and SB-XI susceptible to early and late leaf spot diseases. Resistant interaction was correlated with early and rapid induction of PAL, as evidenced from the enzyme activity. The PAL was expressed differentially in different parts of seedling of all cultivars. However, the response of hypocotyls was maximum in resistant cultivar Girnar-l.